High-entropy oxide ceramic with wave-absorbing and heat-insulating properties and preparation method of high-entropy oxide ceramic

By simultaneously doping elements in perovskite-type high-entropy oxide ceramics and adopting microwave sintering technology, the problem of difficult integration of high-temperature heat insulation and wave absorption performance in the prior art is solved, efficient high-temperature wave absorption and heat insulation performance is achieved, and the preparation cost is reduced.

CN119551980AActive Publication Date: 2025-03-04ZHENGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411738025.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively integrate high-temperature heat insulation and wave absorption properties, and the preparation cost of high-entropy oxide ceramics is relatively high.

Method used

Perovskite-type high-entropy oxide ceramics are used to prepare high-entropy oxide ceramics with high wave absorption and thermal insulation properties by doping elements at the A and B positions simultaneously, and using equimolar doping method, combined with microwave sintering technology.

Benefits of technology

High wave absorption and heat insulation performance at high temperatures are achieved, sintering costs are reduced, and uniform heating and performance improvement of ceramics are ensured through microwave sintering technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551980A_ABST
    Figure CN119551980A_ABST
Patent Text Reader

Abstract

The invention provides high-entropy oxide ceramic with wave-absorbing and heat-insulating properties and a preparation method of the high-entropy oxide ceramic. The chemical formula of the ceramic is ABO3, and the A site contains two elements of Bi and Na and simultaneously contains any two of Ca, Sr and Ba; and the B site comprises any two of Sn, Ti, Zr and Ce. All the elements are equimolar in respective positions. The preparation method comprises the steps of ball milling, drying, calcining, tabletting, microwave sintering and the like. Compared with the prior art, the high-entropy oxide ceramic provided by the invention has excellent wave-absorbing and heat-insulating properties and has the advantage of low preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high entropy ceramic materials, and specifically discloses a high entropy oxide ceramic with both wave absorbing and heat insulating properties and a preparation method thereof. Background Art

[0002] With the rapid development of the aerospace field, the application environment requirements of absorbing materials in aerospace, cruise missiles, hypersonic aircraft and other equipment are becoming more and more stringent. Therefore, new absorbing materials with dual functions of absorbing and high-temperature heat insulation have emerged. At present, few new materials integrating absorbing and heat insulation have been reported, and how to effectively integrate these functions through simple and efficient methods is still a huge challenge. It is crucial to develop materials with excellent high-temperature heat insulation and absorbing properties.

[0003] C / SiC nanofibers have good wave absorption and heat insulation properties, but they do not have excellent wave absorption properties in the X-band. They are easily oxidized at high temperatures of 1200°C, which affects their stability. The carbon / SiO2@CNTs composite aerogel obtained by freeze drying has excellent wave absorption and heat insulation properties, but its cost is very high and it is not suitable for extreme high temperature conditions.

[0004] High entropy oxide ceramics have excellent properties such as huge composition adjustment space, oxidation resistance and high temperature stability. Oxides with high entropy perovskite structure often have extremely low thermal conductivity and excellent high temperature stability, and are expected to be used as absorbing materials in high temperature extreme environments. At present, some technologies can realize the preparation of high entropy oxide ceramics with both absorbing and heat insulating properties. For example, patent CN114853458A discloses a high entropy ceramic and its preparation method and application as an electromagnetic wave absorbing material, with a molecular formula of (Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )Cr2O4 spinel and perovskite high entropy ceramics; Patent CN115504778A discloses a cobalt-based high entropy ceramic and its preparation method and application, the chemical formula is (Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O / Co2O4 spinel and rock salt crystal structure high entropy ceramics. However, the microwave absorption performance of high entropy oxide ceramic materials prepared by these methods needs to be further improved, and the sintering cost is high.

[0005] Therefore, how to prepare high entropy oxide ceramics with high microwave absorption and thermal insulation properties and reduce the preparation cost is a technical problem that needs to be urgently solved in the industry. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a high entropy oxide ceramic having both microwave absorption and thermal insulation properties and a preparation method thereof, wherein the method can obtain a high entropy oxide ceramic having high microwave absorption and thermal insulation properties and has a low preparation cost.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] A high entropy oxide ceramic with both microwave absorption and heat insulation properties, with a chemical formula of ABO3 and a perovskite crystal structure; the A position in the chemical formula contains two elements, Bi and Na, and contains any two of Ca, Sr, and Ba; the B position in the chemical formula contains any two of Sn, Ti, Zr, and Ce; the elements in the A position in the chemical formula have equal molar ratios.

[0009] Furthermore, in the chemical formula of the high entropy oxide ceramic, the elements at the B position have an equal molar ratio.

[0010] A method for preparing a high entropy oxide ceramic having both microwave absorbing and heat insulating properties, characterized in that it comprises the following steps:

[0011] S1. Weigh Bi2O3 and Na2O3 powders, weigh any two of CaCO3, SrCO3, and BaCO3 powders, and weigh any two of SnO2, TiO2, ZrO2, and CeO2 powders to obtain powder raw materials;

[0012] S2. Add anhydrous ethanol and ball milling beads to the powder raw material in step S1, and obtain a mixed powder after ball milling, drying and sieving;

[0013] S3. The mixed powder of step S2 is calcined and tableted to obtain a cold-pressed blank;

[0014] S4. The cold pressed blank in step S3 is subjected to microwave sintering to obtain high entropy oxide ceramics.

[0015] Furthermore, in step S2, the mass ratio of the powder raw material, anhydrous ethanol and ball milling beads is 1:(0.5-1.5):(1-2), the ball milling beads are zirconia, the ball milling speed is 200-300 r / min, and the ball milling time is 6-12 h.

[0016] Furthermore, in step S3, the calcination temperature is 600-800° C., and the calcination time is 2-6 hours.

[0017] Furthermore, in step S3, the tableting pressure is 10-20 MPa, and the tableting duration is 60-300 s.

[0018] Furthermore, in step S4, the microwave frequency is 2.45 GHz, air is used as the sintering atmosphere, and the gas pressure in the sintering chamber is 0.1-0.3 MPa.

[0019] Furthermore, in the microwave sintering process in step S4, the microwave sintering furnace is first heated to 900°C at a rate of 10°C / min, then heated to 1500-1600°C at a rate of 5°C / min, and then cooled to room temperature with the furnace after the insulation is completed.

[0020] Beneficial effects of the present invention: The present invention proposes a high-entropy oxide ceramic with both wave-absorbing and heat-insulating properties and a preparation method, and utilizes microwave sintering to obtain a high-entropy oxide ceramic with high wave-absorbing and heat-insulating properties. Compared with the prior art, the present invention greatly increases the complex structure of the crystal by simultaneously doping at the A and B positions of the perovskite structure and using equimolar doping at the B position, thereby hindering the scattering of phonons therein and improving the heat-insulating properties at high temperatures. Secondly, the present invention only dopes 4-position metal oxides at the A position of the perovskite structure, which significantly increases the melting point and enhances the wave-absorbing properties. In addition, the traditional sintering method has the problem of uneven heating. The present invention uses microwaves for internal heating, and by controlling the heating rate, the entire ceramic can be evenly heated, so that it can achieve high-entropy ceramics with better performance, while greatly reducing the sintering cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0022] Figure 1 This is the XRD diagram of the high entropy perovskite material in Example 1 of the present invention.

[0023] Figure 2 This is the EDS image of the high entropy perovskite material obtained in Example 1 of the present invention.

[0024] Figure 3 This is a high-temperature thermal conductivity diagram from room temperature to 1000°C of the high-entropy perovskite material obtained in Example 1 of the present invention.

[0025] Figure 4 This is a reflection loss diagram of Example 1 of the present invention at different thicknesses.

[0026] Figure 5 This is the impedance matching diagram of the high entropy perovskite material of Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] S1. Weigh Bi2O3, Na2O3, CaCO3, SrCO3, SnO2, and TiO2 powders according to a molar ratio of 0.5:0.5:1:1:2:2 to obtain a powder raw material;

[0030] S2. Anhydrous ethanol and ball milling beads are added to the powder raw material in step S1, and a mixed powder is obtained after ball milling, drying and sieving. The mass ratio of the powder raw material, anhydrous ethanol and ball milling beads is 1:0.5:1, the ball milling beads are zirconium oxide, the ball milling speed is 200 r / min, and the ball milling time is 6 h;

[0031] S3. The mixed powder of step S2 is calcined at 600° C. for 2 h, and then pressed at 10 MPa for 60 s to obtain a cold pressed blank;

[0032] S4. The cold pressed blanks in step S3 are subjected to microwave sintering at a microwave frequency of 2.45 GHz. Air is used as the sintering atmosphere. The air pressure in the sintering chamber is 0.1 MPa. The temperature is first increased to 900°C at a rate of 10°C / min, and then increased to 1500°C at a rate of 5°C / min. The temperature is kept at a temperature for 3 hours. After the temperature is kept at a temperature, the blanks are cooled to room temperature in the furnace to obtain high entropy oxide ceramics.

[0033] After XRD, EDS, high temperature thermal conductivity and reflection loss analysis, the results are attached. Figure 1-5 , successfully prepared high entropy oxide (Bi 0.25 Na 0.25 Ca 0.25 Sr 0.25 )(Ti 0.5 Sn 0.5 )O3, at room temperature, the effective absorption is 3.12GHz at a thickness of 2.8mm, and the reflection loss of this high entropy ceramic can reach 44.6GB at a frequency of 9.2GHz. The room temperature thermal conductivity is 1.19Wm -1 K -1 , with high wave absorption and heat insulation performance.

[0034] Embodiment 2:

[0035] S1. Weigh Bi2O3, Na2O3, CaCO3, SrCO3, SnO2, and TiO2 powders according to a molar ratio of 0.5:0.5:1:1:2:2 to obtain a powder raw material;

[0036] S2. Anhydrous ethanol and ball milling beads are added to the powder raw material in step S1, and a mixed powder is obtained after ball milling, drying and sieving. The mass ratio of the powder raw material, anhydrous ethanol and ball milling beads is 1:1.5:2, the ball milling beads are zirconium oxide, the ball milling speed is 300r / min, and the ball milling time is 12h;

[0037] S3. The mixed powder of step S2 is calcined at 800° C. for 6 h, and then pressed at 20 MPa for 300 s to obtain a cold pressed blank;

[0038] S4. The cold pressed blanks in step S3 are subjected to microwave sintering at a microwave frequency of 2.45 GHz. Air is used as the sintering atmosphere. The air pressure in the sintering chamber is 0.3 MPa. The temperature is first increased to 900°C at a rate of 10°C / min, and then increased to 1600°C at a rate of 5°C / min. The temperature is kept at a high temperature for 6 hours. After the temperature is kept at a high temperature, the blanks are cooled to room temperature in the furnace to obtain high entropy oxide ceramics.

[0039] After XRD, EDS, high temperature thermal conductivity and reflection loss analysis, high entropy oxide (Bi 0.25 Na 0.25 Ca 0.25 Sr 0.25 )(Ti 0.5 Sn 0.5 )O3, at room temperature, with an effective absorption bandwidth of 2.98 GHz at a thickness of 2.8 mm and a frequency of 9.24 GHz, the reflection loss of this high entropy ceramic can reach 36.7 GB. The room temperature thermal conductivity is 1.23 Wm -1 K -1 , with high wave absorption and heat insulation performance.

[0040] Embodiment 3:

[0041] The steps are the same as those in Example 2, except that in step S2, the mass ratio of the powder raw material, anhydrous ethanol and ball milling beads is 1:1:1.5, the ball milling speed is 250 r / min, and the ball milling time is 8 hours; in step S3, the calcination temperature is 700°C, the calcination time is 4 hours, and then the cold pressed blank is obtained at 15 MPa for 200 seconds, and in step S4, the microwave sintering is first heated to 900°C at a rate of 10°C / min, and then heated to 1550°C at a rate of 5°C / min, and the holding time is 4.5 hours. Other conditions are the same.

[0042] After XRD, EDS, high temperature thermal conductivity and reflection loss analysis, high entropy oxide (Bi 0.25Na 0.25 Ca 0.25 Sr 0.25 )(Ti 0.5 Sn 0.5 )O3, at room temperature, with an effective absorption bandwidth of 3.15GHz at a thickness of 2.8mm and a frequency of 9.1GHz, the reflection loss of this high entropy ceramic can reach 40.21GB. The room temperature thermal conductivity is 1.54Wm -1 K -1 , with high wave absorption and heat insulation performance.

[0043] Embodiment 4:

[0044] The steps are the same as those in Example 2, except that in step S1, the oxide raw materials are bismuth oxide, sodium carbonate, strontium carbonate, barium carbonate, titanium oxide, and tin oxide, and the molar ratio is 0.5:0.5:1:1:2:2.

[0045] After XRD, EDS, high temperature thermal conductivity and reflection loss analysis, high entropy oxide (Bi 0.25 Na 0.25 Ba 0.25 Sr 0.25 )(Ti 0.5 Sn 0.5 )O3, at room temperature, with an effective absorption bandwidth of 3.07 GHz at a thickness of 2.6 mm and a frequency of 8.78 GHz, the reflection loss of this high entropy ceramic can reach 39.74 GB. The room temperature thermal conductivity is 2.01 Wm -1 K -1 , with high wave absorption and heat insulation performance.

[0046] Embodiment 5:

[0047] The steps are the same as those in Example 2, except that in step S1, the oxide raw materials are bismuth oxide, sodium carbonate, strontium carbonate, calcium carbonate, titanium oxide, and zirconium oxide, and the molar ratio is 0.5:0.5:1:1:3:1. In step S2, the mass ratio of the powder raw material, anhydrous ethanol, and ball milling beads is 1:1:1.5, the ball milling speed is 300 r / min, and the ball milling time is 12 h.

[0048] After XRD, EDS, high temperature thermal conductivity and reflection loss analysis, high entropy oxide (Bi 0.25 Na 0.25 Ca 0.25 Sr 0.25 )(Ti 0.75 Zr 0.25)O3, at room temperature, with an effective absorption bandwidth of 2.54 GHz at a thickness of 2.6 mm and a frequency of 9.45 GHz, the reflection loss of this high entropy ceramic can reach 32.41 GB. The room temperature thermal conductivity is 1.71 Wm -1 K -1 , with high wave absorption and heat insulation performance.

[0049] Embodiment 6:

[0050] The steps are the same as those in Example 2, except that in step S1, the oxide raw materials are bismuth oxide, sodium carbonate, strontium carbonate, calcium carbonate, titanium oxide, and cerium oxide, and the molar ratio is 0.5:0.5:1:1:1:3. In step S4, microwave sintering is first heated to 900°C at a rate of 10°C / min, and then heated to 1550°C at a rate of 5°C / min, and the holding time is 6h.

[0051] After XRD, EDS, high temperature thermal conductivity and reflection loss analysis, high entropy oxide (Bi 0.25 Na 0.25 Ca 0.25 Sr 0.25 )(Ti 0.25 Ce 0.75 )O3, at room temperature, with an effective absorption bandwidth of 6.45GHz at a thickness of 2.6mm and a frequency of 9.45GHz, the reflection loss of this high entropy ceramic can reach 34.41GB. The room temperature thermal conductivity is 3.24Wm -1 K -1 , with high wave absorption and heat insulation performance.

Claims

1. A high entropy oxide ceramic having both microwave absorption and heat insulation properties, characterized in that: The chemical formula of the high entropy oxide ceramic is ABO3, and the crystal structure is perovskite type; in the chemical formula of the high entropy oxide ceramic, the A position contains two elements, Bi and Na, and also contains any two of Ca, Sr, and Ba; in the chemical formula of the high entropy oxide ceramic, the B position contains any two of Sn, Ti, Zr, and Ce; in the chemical formula of the high entropy oxide ceramic, the elements in the A position have equal molar ratios.

2. The high entropy oxide ceramic having both microwave absorption and heat insulation properties according to claim 1, characterized in that: In the chemical formula of the high entropy oxide ceramic, the elements at the B position have an equal molar ratio.

3. A method for preparing a high entropy oxide ceramic having both microwave absorption and heat insulation properties as claimed in claim 1 or 2, characterized in that: The steps include: S1. Weigh Bi2O3 and Na2O3 powders, weigh any two of CaCO3, SrCO3, and BaCO3 powders, and weigh any two of SnO2, TiO2, ZrO2, and CeO2 powders to obtain powder raw materials; S2. Add anhydrous ethanol and ball milling beads to the powder raw material in step S1, and obtain a mixed powder after ball milling, drying and sieving; S3. The mixed powder of step S2 is calcined and tableted to obtain a cold-pressed blank; S4. The cold pressed blank in step S3 is subjected to microwave sintering to obtain high entropy oxide ceramics.

4. The method for preparing a high entropy oxide ceramic having both microwave absorption and heat insulation properties according to claim 3, characterized in that: In the step S2, the mass ratio of the powder raw material, anhydrous ethanol and ball milling beads is 1:(0.25-1):(1-2), the ball milling beads are zirconium oxide, the ball milling speed is 200-300 r / min, and the ball milling time is 6-12 h.

5. The method for preparing a high entropy oxide ceramic having both microwave absorption and heat insulation properties according to claim 3, characterized in that: In step S3, the calcination temperature is 600-800° C. and the calcination time is 2-6 hours.

6. The method for preparing a high entropy oxide ceramic having both microwave absorption and heat insulation properties according to claim 3, characterized in that: In step S3, the tableting pressure is 10-20 MPa, and the tableting duration is 60-300 s.

7. The method for preparing a high entropy oxide ceramic having both microwave absorption and heat insulation properties according to claim 3, characterized in that: In step S4, the microwave frequency is 2.45 GHz, air is used as the sintering atmosphere, and the gas pressure in the sintering chamber is 0.1-0.3 MPa.

8. The method for preparing a high entropy oxide ceramic having both microwave absorption and heat insulation properties according to claim 3, characterized in that: The microwave sintering process in step S4 is to first heat the microwave sintering furnace to 900°C at a rate of 10°C / min, then heat it to 1500-1600°C at a rate of 5°C / min, then keep it warm for 3-6 hours, and then cool it to room temperature with the furnace after the heat preservation is completed.

Citation Information

Patent Citations

  • Preparation method of sintered transition metal high-entropy ceramic oxide composite material

    CN112876237A

  • (ZrTiCoNb) C high-entropy carbide ceramic material and preparation method thereof

    CN113582696A

  • Perovskite structure high-entropy dielectric ceramic and preparation method thereof

    CN114644523A

  • High-entropy perovskite type electromagnetic wave absorbing material and preparation method thereof

    CN116282214A